Precocious Puberty: Etiology and Current Treatment - Jihan Alifa Rahma; Adinda Ilsa Maulida; Alma Dyah Perwita; Baiq Ayu Rahmawati; Clara Nadila; Herodya Lajunee Fesmia; Ni Made Utami Wulandari; Zhayyin Palna Rial Novsyaini; Indana Eva Ajmala (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Precocious puberty also known as premature puberty is an abnormal pubertal development that can affect a child's growth and development. The clinical manifestations of precocious puberty are generally diverse and based on etiology are classified into central precocious puberty (GnRH dependent) and peripheral precocious puberty (GnRH independent). The main concern with precocious puberty is that precocious puberty can be a clinical symptom of an underlying serious disease such as a brain tumor, adrenal or gonadal tumor and others. Early identification of etiology plays an important role in prevention, diagnosis, and treatment of this disease. This literature review aims to determine the etiology and current management of precocious puberty. This literature review uses the keywords